Implementation of android versatile drive interface in a vehicle model - Ahmad Nazirul Ariff, A. Majid (2016)
Versatile Drive Interface is important as a platform to the user to monitor the health of the car and as an infotainment to controlling the interior features of the vehicle. Furthermore the increase of the number of vehicles on the road is proportional to the increase of the vehicle's services. With the data provided by the on board diagnostic system in the vehicle can let the users somehow notice the vehicle's problems and can prevent or predict the next service. With more complex and advance technologies in the automotive industries means more features will be add into a vehicle and with the help of the Versatile Drive Interface (VDI), users are know more convenient to control the features from inside or outside of their vehicles. This, on one hand, allows for providing more convenient and modern method by implement the Android technology This thesis involved the design process and the development process of the Android based software application and the hardware part and more focusing on the local manufactured vehicle in Malaysia. Finally, this thesis present a prototype of the implementation of a Versatile Drive Interface (VDI) in a vehicle model.